Profile of Scaffolding Transfer in STEM-Based Open Inquiry Learning for Electromagnetics Practicum - Riantoni, Cicyn; Rusdi, Rusdi; Maison, Maison; Yelianti, Upik (STAI Hubbulwathan Duri, 2024)
In the context of STEM-based open inquiry learning, scaffolding transfer involves providing assistance that enables students to explore, experiment, and investigate problems or questions independently. The purpose of this study was to determine the profile of scaffolding transfer in STEM-based open inquiry learning during an electromagnetics practicum. This research used a qualitative method with a participatory observation design. The research subjects were 34 students who participated in the electromagnetics practicum. The research instruments consisted of observation guides and field notes. Data were collected through direct observation during the practicum and the analysis of related documents. Data analysis was conducted through coding to identify scaffolding patterns and their transfer. The results showed that there are variations in the percentage of scaffolding provided in STEM-based open inquiry learning on different topics. This variation reflects the dynamics of changing student needs along with the complexity of the material. These results also show that scaffolding is dynamic because the level of support can increase again when students encounter new concepts or difficult concepts. In addition, the highest scaffolding in the open inquiry process occurs at the “asking questions” stage, which indicates a great need for help at the beginning of learning. In contrast, no scaffolding was provided at the stage of “communicating the results of the investigation,” which reflects students' independence.